Control Platform for Multiphase Motors - Kozovský, Matúš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This article focuses on the design and subsequent implementation platform for controlling multi-phase motors. Article describes the functionality of the assembled platform and the possibility of its usage to control either the individual motors or a single multi-phase motor. Platform is able to control Maximum nine-phases motor. The platform uses the three core AURIX TriCore microcontroller TC275. This paper also describes the distribution control program to initialization of device and separated control application generated by the Simulink automatic code generation. Finally interconnection these partial programs into a single control application.
Keywords: TC275; AURIX; TriCore; nine-phases power stage